1998
DOI: 10.1002/(sici)1096-9136(199804)15:4<334::aid-dia575>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes mellitus and associated cardiovascular risk factors in an adult urban population in Paraguay

Abstract: A cross-sectional study was conducted on a 20-74-year-old population in an urban white-Hispanic population in Paraguay to determine the prevalence of diabetes mellitus (DM), impaired glucose tolerance (IGT), and associated cardiovascular disease (CVD) risk factors. In total 1606 subjects completed the study (response rate 80.3%; 1094 women, 512 men). The overall prevalences were: DM 6.5%, IGT 11.3%, hypertension 17.1%, and obesity 31.6% with more obesity in women (35.7% vs 22.8%, p < 0.05). Age-standardized pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
5
Order By: Relevance
“…Using OGTT as a screening instrument, the observed prevalences of diabetes and IGT in our sample of obese people were 20.1 and 22.9%, respectively. This is higher than that reported for the Italian general population[11–16], and for population samples of obese subjects[16–18]. The sample consisted of patients seeking weight loss therapy, and may not be representative of obese subjects in the general population.…”
Section: Discussionmentioning
confidence: 76%
“…Using OGTT as a screening instrument, the observed prevalences of diabetes and IGT in our sample of obese people were 20.1 and 22.9%, respectively. This is higher than that reported for the Italian general population[11–16], and for population samples of obese subjects[16–18]. The sample consisted of patients seeking weight loss therapy, and may not be representative of obese subjects in the general population.…”
Section: Discussionmentioning
confidence: 76%
“…La prevalencia es la siguiente en Latinoamérica; Argentina 28,1%, Brasil 30%, Chile 33,7 %, Colombia 23%, Ecuador 28,7%, México 30,8%, Perú 2,3 24%, Uruguay 33%, Venezuela 33%. En nuestro país la prevalencia estimada es 35% .…”
Section: Introductionunclassified
“…For comparison, an earlier study in Mexico City found a rate of 10.7% [6], and rates in urban South American populations have ranged from 6.5-7.6% [7-10]. …”
Section: Introductionmentioning
confidence: 99%